Effects of ethanol, acetaldehyde, and acetic acid on histamine secretion in guinea pig lung mast cells - Ruiz, C. M.; Gomes, J. C. (Elsevier B.V., 2000)
We studied the direct effects of ethanol and its metabolites on the guinea pig lung mast cell, and the alterations caused in the histamine release induced by different stimuli. Guinea pig lungs cells dispersed by collagenase were used throughout. High concentrations of ethanol (100 mg/ml), acetaldehyde (0.3-3 mg/ml) and acetic acid (3 mg/ml) induced histamine release that was not inhibited by sodium cyanide (0.3 mM). Lower concentration of ethanol (10 mg/ml) and acetic acid (0.3 mg/ml), but not acetaldehyde, inhibited the histamine release induced by antigen and ionophore A23187. The histamine release induced by phorbol 12-miristate 13-acetate (1 mu M) was also inhibited by ethanol (10 mg/ml). Changes in the levels of calcium, glucose and phosphatidic acid did not influence the effect of ethanol. We conclude that high doses of ethanol, acetaldehyde, and acetic acid cause a cytotoxic histamine release by independent mechanisms. Low concentrations of acetic acid inhibit the histamine release by pH reduction. Ethanol acts by a generalized effect that is independent of calcium and glucose suggesting a nonspecific effect that, nevertheless, is not cytotoxic since it can be reversed by washing the cells. (C) 2000 Elsevier B.V. All rights reserved.
Keywords: histamine release; mast cells; ethanol; guinea pig